Further parasites of the family garniidae (Coccidiia: Haemosporidiiea) in Brazilian lizards. Fallisia effusa gen.nov., sp.nov. and Fallisia modesta gen.nov., sp.nov - Lainson, Ralph (2016)
Minist?rio da Sa?de. Funda??o Servi?o de Sa?de P?blica. Instituto Evandro Chagas. Bel?m, PA, Brasil.